THE ROLE OF INTERNET BANKING FACILITIES & SYSTEM QUALITY ON CUSTOMER SATISFACTION AT PT BCA TBK BRANCH KCP TAMAN SEMANAN INDAH JAKARTA - Adhani, Ida (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2023)
This study aims to examine the effect of internet banking facilities and system quality as an accounting information system on customer satisfaction partially or simultaneously. The data used is the main data in the form of a questionnaire with a total sample of 60 respondents from Bank BCA KCP Taman Semanan Indah, Kalideres, West Jakarta. The data analysis technique used is multiple linear regression, classical assumption testing, and hypothesis testing. The results showed that internet banking facilities (X1) and system quality (X2) had an effect on customer satisfaction (Y) both partially and simultaneously. The adjusted R square value is 51.7%, meaning that the customer satisfaction variable is influenced by the internet banking facility and system quality variables, various factors can impact the remaining part.